Analysis of Investor Sentiment Impact in Indonesia Composite Stock Price Index Return Volatility - Rum Puspita Widhiarti; Lukytawati Anggraeni; Syamsul Hidayat Pasaribu (Indonesian Journal of Business and Entrepreneurship (IJBE), 2018)
The Composite Stock Price Index (IHSG) is an index used as an indicator of stock price movements on Indonesia Stock Exchange and reference of capital market activities. Stock securities have high risk because they do not have maturity such as bonds so volatility is one of the important things in stock investment. Investor sentiment is one of many external factors that affecting stocks volatility. Investor sentiment is one of behavioral finance assumptions which may cause systematic risk with noise so it affects stocks volatility. Therefore it is necessary to analyze the development of investor sentiment and its impact on IHSG volatility. This study used Business Tendency Index as investor sentiment proxy and monthly IHSG. Bank Indonesia Certificates is used to get excess return. GJR-GARCH method is used in this study along the periode from January 2001 to December 2015. The results showed that there is significant effect of investor sentiment on excess return. As investors are optimistic, the uncertainty in stock market will increase while IHSG volatility will increase as the average investor is pessimistic. There is noticeable leverage effect in the presence of negative shocks resulting in higher conditional variance changes compared to positive shocks on the same magnitude.Keywords: volatility, investor sentiment, GJR-GARCH, behavioral finance, IHSG